Pengaruh Blended Learning terhadap Hasil Belajar Mahasiswa Jurusan Biologi FMIPA Universitas Negeri Makassar - Adnan Adnan; Andi Rahmat Saleh; Dian Dwi Putri Ulan Sari Patongai; Suhardi Aldi (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Student learning outcomes are still a challenge in higher education, especially in a learning system that is still teacher-centered and lack interactivity. Therefore, it is necessary to improve the quality of learning through more responsive and flexible approaches, such as blended learning. This study aims to analyze the effect of implementing blended learning on the learning outcomes of biology students in the Faculty of Mathematics and Natural Sciences (FMIPA) at the University of Makassar (UNM). This study employed a quasi-experimental design with random sampling. The study population consisted of all Biology Department students at FMIPA UNM enrolled in the Cell and Molecular Biology course. The sample comprised 75 students divided into three classes: two experimental classes and one control class. The assessment instrument used was a learning outcome test in the form of multiple-choice questions. Data analysis was conducted descriptively and inferentially using a one-way ANOVA test. The results showed that Experimental Class 1, which implemented blended learning, achieved a higher average learning outcome score compared to Experimental Class 2 and the control class. The ANOVA test indicated a significant difference between the groups (p < 0.05). Thus, blended learning has a significant effect on student learning outcomes.